Bionomics of transverse ladybird beetle, Coccinella transversalis on cowpea aphid, Aphis craccivora - RAKSHITH, H S; SUROSHE, SACHIN S; CHANDER, SUBHASH; BHAGYASREE, S N; VENKANNA, Y (The Indian Journal of Agricultural Sciences, 2021)
Cowpea aphid, Aphis craccivora Koch is one of the important pests of legumes. It is a cosmopolitan and polyphagous pest causing 30-35% damage to vegetable crops globally. Chemical control of this pest is not only expensive but also has deleterious effects on human health, environment and non-target organisms. Biological control is one of the most important components of integrated pest management to achieve eco-friendly and sustainable management of crop pests. Coccinellid predator, Coccinella transversalis Fab. is an efficient predator known for its appetite on cowpea aphid under vegetable ecosystem. With this background, we conducted a study on biology, morphometric and functional response of C. transversalis on cowpea aphid under laboratory conditions (27Â±1Â°C and 65Â±5% RH) at Biological Control Lab, ICAR-Indian Agricultural Research Institute, New Delhi, during 2016-17. Type of functional response was determined through polynomial logistic regression of proportion of prey consumption to the density of prey. Functional response parameters were obtained by fitting the data to the Holling’s and Roger’s equations. Total life span of male and female was ranged from 47-64 and 60-71 days, with a mean of 56±6.2 and 66±3.9 days, respectively. Both male and female of C. transversalis were found to exhibit Type II functional response. Female has showed high attack rate (1.99±0.141) compared to male (1.90±0.088) with maximum prey consumption of 84.41 and 80.51 aphids/day, respectively. Handling time obtained for males (0.0124 day) was higher than females (0.0118 day).